Interdisciplinarity and the Prior Knowledge Profile Examination - Carmen Oñate Gómez; Manuel Barrero Ripoll; Francisco Sierra Gómez (Universidad Autónoma de Baja California, 2009)
This article presents an activity that has been for years a common assignment for professors and students at the beginning of the school year at the Technical University of Madrid (UPM, for its acronym in Spanish Universidad Politécnica de Madrid): the Knowledge Profile Examination. Among the many variables this examination has, interdisciplinarity is one of the most significant ones. This remarkable meta-cognitive variable, which urgently needs to be studied, researched, solved and qualified, undoubtedly provides the best contributions to the quantity-quality intricacy of knowledge. The solution of the most important pedagogical issues in the coming years depends on it, when the development of a more humane, useful and responsible knowledge at universities is aimed.